Multielement extraction from aqueous solutions by palm kernel fatty acid distillate / Jenifer Dennis and Chang Siu Hua - Dennis, Jenifer; Chang, Siu Hua (2021)
Palm kernel fatty acid distillate (PKFAD) was investigated into its potentiality as green extractant for Cu(II), Ni(II), Co(II), Mn(II) and Au(III) extraction from aqueous solutions. The pH-extraction isotherms of various elements by PKFAD were studied at a constant O:A ratio of 1:1. The separation factors of Cu(II) over other elements at pH 4.7 and different O:A ratios (1:1, 2:1, 3:1, 5:1, 10:1) were also studied. Results revealed that the highest Cu(II) (98%), Ni(II) (67.21%), Co(II) (62.38%), Mn(II) (96%) and Au(III) (99%) were achieved at pH 4.7, O:A of 1:1, inert salt concentration of 200 mM and temperature of 25°C. The extraction selectivity of Cu over other elements in descending order was Ni>Co>Mn>Au throughout the different extraction conditions studied. Therefore, PKFAD is a potential green organic solvent for the extraction of different elements from aqueous solutions.